Efficient Removal of Nickel, Zinc, Chromium, and Cobalt from Acid Mine Drainage using Constructed Wetlands: Impact of Vegetation and Hydraulic Retention Time - Anand, Nongmaithem; Devi, Konsam Rambha (Engineering, Technology & Applied Science Research, 2025)
This study evaluates the effectiveness of Constructed Wetlands (CWs) in treating Acid Mine Drainage (AMD), focusing on the removal of Ni, Zn, Cr, and Co. Two CW configurations were tested: CW-I (unplanted) and CW-II (planted with Alocasia odora and Spirodela polyrhiza). Over 12 months, both systems operated at Hydraulic Retention Times (HRTs) of 24, 48, and 72 hours. CW-II consistently outperformed CW-I, achieving 88.1% Zn and 67.8% Cr removal at 72 hours. Ni removal improved to 44.3%, while Co, though less effectively removed, reached 28.3%. . The statistical analysis confirmed that both HRT and vegetation significantly influenced metal removal efficiencies. The enhanced performance of CW-II highlights the critical role of phytoremediation in the pollutant uptake. These findings demonstrate that vegetated CWs offer a scalable, eco-friendly alternative for AMD treatment, with potential applications in broader environmental remediation efforts. Further research should focus in plant optimization, real-world validation, and substrate and system design.